Personality Type and the Male Experience of Identity in Midlife: Implications for Counselling and Psychotherapy - Rob Brandenburg; Kurt Lushington (Psychotherapy and Counselling Journal of Australia)
A better understanding of the role of personality type on the male experience of midlife is thought to be of value when providing counselling and psychotherapy support to men, but to date there are few available resources in this area. Based on the Myers-Briggs Type Indicator®, the pilot study compared ten males aged 40-55 years with a preference for Intuitive-Feeling with ten with a Sensing-Thinking preference. The majority of both personality types reported a smooth transition into midlife with several gains including increased life mastery, greater self-awareness and enhanced intimacy in relationships. However, men in the Sensing-Thinking group compared with those in the Intuitive-Feeling group were more likely to have experienced an existential crisis, viewed their self/masculine identity primarily in terms of career/work and were less likely to have experienced increased intimacy with their spouse or partner in midlife. The tentative findings of this pilot study suggest that personality may influence the male experience of midlife.